2023
DOI: 10.3390/plants12162979
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Metabolic Characterization of Flowers and Hips of Rosa gallica L. Grown in Open Nature

Nina Kunc,
Metka Hudina,
Maja Mikulič-Petkovšek
et al.

Abstract: Our research aimed to investigate the primary and secondary metabolites of rosehips and petals of R. gallica in comparison with R. subcanina. R. gallica was chosen because it is still unexplored in terms of various bioactive substances and is strongly present in Slovenia. Given that roses are generally very variable and unstudied, our research will contribute to greater transparency and knowledge of the bioactive composition of rosehips and petals. We found a strong positive correlation between the total conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
0
2
Order By: Relevance
“…Such lower levels in this study are most likely a result of the well-maintained rose bushes in the park from which the samples were obtained, and these conditions represented a lower exposure for one plant. Compared to the rose hip samples of R. gallica from a cultivated park analyzed in this experiment, it is observed that the rose hips of R. gallica from na-ture reported by Kunc et al [43] had a higher carotenoid content (32.39 mg/100 g FW) in the same year. Kunc et al [43] also concluded that the reported carotenoid levels are at a lower limit compared to those reported in the literature and that there is still potential for higher carotenoid levels.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Such lower levels in this study are most likely a result of the well-maintained rose bushes in the park from which the samples were obtained, and these conditions represented a lower exposure for one plant. Compared to the rose hip samples of R. gallica from a cultivated park analyzed in this experiment, it is observed that the rose hips of R. gallica from na-ture reported by Kunc et al [43] had a higher carotenoid content (32.39 mg/100 g FW) in the same year. Kunc et al [43] also concluded that the reported carotenoid levels are at a lower limit compared to those reported in the literature and that there is still potential for higher carotenoid levels.…”
Section: Discussioncontrasting
confidence: 40%
“…Compared to the rose hip samples of R. gallica from a cultivated park analyzed in this experiment, it is observed that the rose hips of R. gallica from na-ture reported by Kunc et al [43] had a higher carotenoid content (32.39 mg/100 g FW) in the same year. Kunc et al [43] also concluded that the reported carotenoid levels are at a lower limit compared to those reported in the literature and that there is still potential for higher carotenoid levels. Such differences occur due to genetic variability, agrometeorological conditions, growing conditions, storage, and differences in maturity, in addition to technological differences [33].…”
Section: Discussioncontrasting
confidence: 40%